"A Woman in A Man's World": A Pilot Qualitative Study of Challenges Faced by Women Veterans During and After Deployment. Issue 2 (15th March 2021) - Brown, Elaine K.; Guthrie, Kate M.; Stange, Mia; Creech, Suzannah
ABSTRACT: Women Veterans face gender-specific challenges to military life and post-deployment readjustment, including gender-based discrimination and military sexual trauma. Despite recent military initiatives to address these issues, women still experience unique challenges during military service. This study examines spontaneous comments about gender-specific challenges to military life that were made by participants in a qualitative study of women's transitions to civilian life after deployment to Iraq or Afghanistan. Methods: Women Veterans who were enrolled at a New England VA hospital and who had deployed to the U.S. conflicts in Iraq and Afghanistan participated in this qualitative study (N = 22). Interview queries and initial coding structure were developed through an extensive literature review. An iterative coding process generated additional themes identified in the data. For this project, codes regarding self-initiated reports of gender-specific challenges that fell outside the scope of the study's initial interview agenda were reviewed for thematic analysis. Results: The following three self-initiated themes emerged among 12 respondents: 1) gender-based scrutiny and discrimination; 2) the military's inadequate position and response to military sexual trauma; and 3) disadvantages to women service members living in a male-dominated environment. Across all three themes emerged a sub-theme in which women perceived their unique needs to be inconvenient and/or disregarded. Respondents described how these challenges disrupted their lives during and after military service. Conclusion: Results imply gender-specific challenges and military sexual trauma remain critical concerns for women Veterans well after deployment had ended, and that improved policy may have long-term health implications.